Suberin utilization by chrysonilia sitophila: evidence for lipolytic enzymes production - Vitorino,S. I. (2007)
The role of the development of Chrysonilia sitophila on cork slabs, during the manufacturing process of cork stoppers, is not clearly understood. This work describes the first results demonstrating the potential of that mould to metabolize suberin. Lipolytic activity was clearly observed in solid and liquid cultures of C. sitophila.